Interactive CovidCampus Simulation Game: Genesis, Design, and Outcomes - Johnson-Glenberg, Mina C.; Jehn, Megan; Chung, Cheng-Yu; Balanzat, Don; Nieland Zavala, Ricardo; Apostol, Xavier; Rayan, Jude; Taylor, Hector; Kapadia, Anoosh; Bartolomea, Hannah (Frontiers in Communication, 2021)
We explore how an AR simulation created by a multidisciplinary team evolved into a more interactive, student-centered learning game. The CovidCampus experience was designed to help college students understand how their decisions can affect their probability of infection throughout a day on campus. There were eight decision points throughout the day. Within group comparisons of immediate learning gains and self-reported behavioral changes were analyzed. Results revealed a significant increase in confidence in asking safety-related questions. Post-play, a significant majority of players listed new actions they would take to increase their safety; players were more agentic in their choices. This game allowed players to go back and replay with different choices, but only 7% chose to replay. Short, interactive desktop games may be an effective method for disseminating information about how to stay safer during a pandemic. The game appeared to positively change most players’ health behaviors related to mitigation of an infectious disease. Designers of interactive health games should strive to create multi-disciplinary teams, include constructs that allow players to agentically make decisions, and to compare outcomes over time.